Literature review on pyrethroid common metabolites. Issue 12 (17th December 2021) - Greene, Tracy; Salley, Joshua; Polcher, Alexandra; Gentry, Robinan; Rücker, Thomas
Abstract: A systematic literature review has been performed on the toxicological profiles of the pyrethroid common metabolites 3‐phenoxybenzoic acid (PBA), 3‐(4'‐hydroxyphenoxy)benzoic acid (PBA(OH)) and 3‐phenoxybenzaldehyde (PBAld). Following the definition of appropriate search strings 1031 publications were screened by abstract, title and keywords followed by a screening of full texts of 82 publications. From these 20 publications could be identified to provide data relevant for the toxicological profile(s) of one or more of the metabolites. As one publication covered in vitro and in vivo studies those data have been assessed twice – so that the total number of publications was considered to be 21. Overall, the studies identified in the literature focused on effects related to reproductive toxicity, immunotoxicity, endocrine disruption, hepatotoxicity, cardiovascular toxicity, and neurotoxicity. Following a risk of bias (ROB) assessment, the majority (n=13) was considered to have low ROB, while two studies were assessed to have a high ROB. Seven publications could not be allocated to Tier 1 (low risk of ROB) or Tier 3 (high risk of ROB) and thus were grouped as Tier 2 studies. The Tier 1 studies provided evidence that PBA does not appear to produce any effects on sperm motility. However, based on the Tier 1 studies, all of which were in vitro, there are some indications that PBA, PBAld and PBA(OH) may interact with the endocrine system. In addition, also based on in vitro data, PBA and PBAld were shown to produce cell cycle arrest, inhibition of cell differentiation, and generation of reactive oxygen species, indicating the potential for immunotoxicity. PBA was also associated with apoptosis and replicative DNA synthesis in hepatocytes, while PBA along with PBAld damage in heart cells. © European Food Safety Authority, 2021